Cartographic representation of characteristics of population of Jfara region (An applied study using GIS technology) (Journal of Libya for geographical studies, 2023)
study aims to prepare, produce population digital maps for som characteristics of population in Al-Jaffara region, and highlight  spatial ,temporal numerical, relative and townsman variation, and places of concentration and dispersion according to branches and shops due to importance of this in social and economic planning, according to  statistics of census of (2006), and estimates for the year (2020). study tracked the absolute and relative spatial changes that occurred in population size, and its cartographic representation based on      ARC GIS 10.8 Geographic Information Systems program, based on three methods of cartographic representation, so researcher used to calculate the numerical and environmental distribution of population of shops using point distribution method, because it higher visual perception was achieved than color gradient distribution or graphic representation, and gradient method in symbol sizes was used to represent general density, taking into account changing the symbol size to match scale of map.  also showed possibility of representing statistical data in one map in more than one way, by following method of merging  Between the two methods of color gradient distribution (corropleth)  to represent absolute numbers ,and suitable method of symbol size for the value or statistical percentage it represents to represent relative values, to higher visualperception achieve   that gives clear picture to non-specialist reader of spatial variation of distribution. study concluded more than two-thirds of   population of the  Jafara region are concentrated in less than two-thirds of its area, which indicates their distribution is uneven, and their concentration almost same for all branches during study period, and general density varies from one census to another and from one place to another. This according to geographical location of each branch, level of services it enjoys, and its proximity to Tripoli, where the general density increases in Janzour branch, then in northern part of Zahraa branch, then Al- Sawani branch, and northeastern part of Arba'a branch, while decreases in southern and southeastern ends of branch, and also decreases in the Aziziyah branch, especially   southern and southwestern ends.
Keywords: cartographic representation; geographic information systems; general population densit